Biosolids accumulation and biodegradation of domestic wastewater treatment plant sludge by developed liquid state bioconversion process using a batch fermenter - Alam, Md. Zahangir; Fakhru'l-Razi, A.; Molla, Abul H. (Elsevier Science, 2003)
The biosolids accumulation and biodegradation of domestic wastewater treatment plant (DWTP) sludge by filamentous fungi have been investigated in a batch fermenter. The filamentous fungi Aspergillus niger and Penicillium corylophilum isolated from wastewater and DWTP sludge was used to evaluate the treatment performance. The optimized mixed inoculum (A. niger and P. corylophilum) and developed process conditions (co-substrate and its concentration, temperature, initial pH, inoculum size, and aeration and agitaion rate) were incorporated to accelerate the DWTP sludge treatment process. The results showed that microbial treatment of higher strength of DWTP sludge (4% w/w of TSS) was highly influenced by the liquid state bioconversion (LSB) process. In developed bioconversion processes, 93.8g/kg of biosolids was enriched with fungal biomass protein of 30g/kg. Enrichment of nutrients such as nitrogen (N), phosphorous (P), potassium (K) in biosolids was recorded in 6.2% (w/w), 3.1% (w/w) and 0.15% (w/w) from its initial values of 4.8% (w/w), 2.0% (w/w) and 0.08% (w/w) respectively after 10 days of fungal treatment. The biodegradation results revealed that 98.8% of TSS, 98.2% of TDS, 97.3% of turbidity, 80.2% of soluble protein, 98.8% of reducing sugar and 92.7% of COD in treated DWTP sludge supernatant were removed after 8 days of microbial treatment. The specific resistance to filtration (SRF) in treated sludge (1.4×1012m/kg) was decreased tremendously by the microbial treatment of DWTP sludge after 6 days of fermentation compared to untreated sample (85×1012m/kg).